Peran Pemerintah Provinsi Dki Jakarta Dalam Pemberdayaan Pendidikan Di Era Pandemi Covid-19 Tahun 2020 - Cahyo Azmi Fachru'ddin Azmi; Sakir; Fairuz Arta Abhipraya (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2022)
This article discusses the role of the Jakarta Provincial Government in empowering education during the pandemic. The COVID-19 pandemic entered Indonesia and has had a significant impact on several sectors, including the economy, tourism, socio-cultural issues, and education. The enactment of educational policies has significantly impacted teaching and learning programs in the Special Capital Region of Jakarta. One such policy is large-scale social restrictions, which have resulted in all teaching and learning activities, previously conducted in schools, being conducted online. There are several advantages to conducting online teaching and learning activities, including increasing learning independence, interest, and motivation. However, these advantages also have disadvantages, including consuming large data quotas, weak internet signals because not all students live in strategic areas, and time differences in each region, making it difficult to coordinate learning times. The role of the Jakarta Provincial Government in empowering education will significantly assist students in teaching and learning activities during the current pandemic. This study aims to determine the role of the Jakarta Provincial Government in empowering education and its impacts. The author used a qualitative research method with information gathered from the internet.